Modular design of up-to-date flachining syste1s the conception and development results - Rekecki, Jožef; Zeljković, Milan; Borojev, Ljubomir; Gatalo, Ratko; Hodolič, Janko (Journal of Production Engineering, 1989)
The paper presents one of the concepts related to modular design in machining systems. The focus is directed towards the outcomes of modular design in turning machines and machine tools for grinding. The presented results are closely related to the research efforts aimed at establishing the concept, which has been carried out over several years at the Institute for Production Engineering.